1999
DOI: 10.1111/j.1528-1157.1999.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Memory Impairment in Patients with Temporal Lobe Epilepsy: Relation to the Presence, Type, and Location of Brain Lesion

Abstract: Summary:Purpose: To study the influence of epileptogenic lesions on learning and memory alterations in patients with temporal lobe epilepsy (TLE).Methods: We studied 131 patients (55 with left and 39 with right lesional TLE; 22 with left and 15 with right cryptogenic TLE) and 36 healthy subjects. We compared these groups by using a battery of tests to assess verbal and visual learning, delayed recall, and recall after the imposition of interfering activity.Results: Compared with the controls and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
59
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 34 publications
11
59
0
5
Order By: Relevance
“…Notably, the similar results are observed irrespective of epilepsy form, i.e. as in cryptogenic, as in symptomatic temporal lobe epilepsy (Giovagnoli & Avanzini, 1999). In other words, the brain organic lesion itself, including mesiotemporal sclerosis, isn't enough to explain aforementioned discrepancies in hemisphere functions.…”
Section: Asymmetry In Neuropsychological Tests For Verbal and Gestaltsupporting
confidence: 69%
See 1 more Smart Citation
“…Notably, the similar results are observed irrespective of epilepsy form, i.e. as in cryptogenic, as in symptomatic temporal lobe epilepsy (Giovagnoli & Avanzini, 1999). In other words, the brain organic lesion itself, including mesiotemporal sclerosis, isn't enough to explain aforementioned discrepancies in hemisphere functions.…”
Section: Asymmetry In Neuropsychological Tests For Verbal and Gestaltsupporting
confidence: 69%
“…The left hemisphere seems to be responsible as for analytic and verbal, as for gestalt function, while the right hemispherestrictly for gestalt functions. Based on their findings authors concluded that lateralization of brain functions concerns strictly the verbal, but not the visual functions (Giovagnoli & Avanzini, 1999). Concluding this part of article we may suggest that TLE with left foci is more virulent than with right foci, because it causes deterioration as in verbal, as in nonverbal functions.…”
Section: Asymmetry In Neuropsychological Tests For Verbal and Gestaltmentioning
confidence: 87%
“…Several authors, however, found no learning and memory deficits in MTLE patients with unilateral lesions located on the right hemisphere, although confirming the existence of episodic learning and memory deficits for verbal content in MTLE affecting the left hemisphere [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 97%
“…Verbal or visuoconstructive memory dysfunction has been found in patients with left temporal epilepsy or right temporal epilepsy, respectively (4). In preclinical studies, spatial memory of temporal lobe epileptic rats is shown to be compromised (5,6).…”
mentioning
confidence: 99%